The Effect of Intellectual Capital, Corporate Social Responsibility, Good Corporate Governance, and Financial Technology on Financial Performance - Rusma Nailiah; Aisya Aulia Rizki; Fahmi Rizani; Kadir Kadir (Basic and Applied Accounting Research Journal, 2025)
Background: Financial performance is a key indicator of a bank's efficiency and sustainability. The role of Intellectual Capital, Corporate Social Responsibility, Good Corporate Governance, and Financial Technology in enhancing bank performance has become increasingly important, especially in the Indonesian banking sector during periods of economic fluctuation. Purpose: This study aims to examine the effects of Intellectual Capital, Corporate Social Responsibility, Good Corporate Governance, and Financial Technology on the financial performance of banks listed on the Indonesia Stock Exchange between 2021 and 2024. Methods: A total of 33 banks were selected using purposive sampling. Data were analyzed using multiple linear regression in IBM SPSS Statistics 27, with Return on Assets (ROA) serving as the proxy for financial performance. Results: The findings indicate that Intellectual Capital and Financial Technology have a significant positive effect on ROA, whereas Corporate Social Responsibility and Good Corporate Governance do not significantly influence this measure. Conclusion: Intellectual Capital and Financial Technology are critical drivers of financial performance in Indonesian banks. Banks should prioritize these factors to enhance efficiency and profitability, while further research is needed to explore the role of CSR and GCG in different contexts.